Pemikiran dan harapan tentang negara hukum - Baramuli, A.A. (Ahmad Arnold), 1930- (Ciputat, Jakarta : Pustaka Manikgeni, 1997)
Administrative law, Indonesia; articles
Includes index
Keywords: Administrative law -- Indonesia